Perancangan UI/UX Aplikasi Sistem Informasi Pariwisata Kabupaten Jepara Menggunakan Metode Design Thinking - Annisa Rachman; Joko Sutopo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2024)
Jepara Regency is one of the regencies in Central Java that has great tourism potential. However, this potential has not been fully exploited due to a lack of information and promotion. To address this issue, a tourism information system application is needed that can provide complete and accurate information and promotion to tourists. This study uses the design thinking method to design the UI/UX of the tourism information system application of Jepara Regency. This method was chosen because it can involve users in the design process to produce a product that meets the needs and desires of users. The results of the study show that the designed tourism information system application of Jepara Regency has a user-friendly and responsive UI/UX. The application is also equipped with various features that can make it easy for tourists to get information and promotion about tourism in Jepara Regency.